The Relationship between Body Mass Index and Blood Pressure Control in Hypertension Patients at the Sukawati I Community Health Center, Gianyar Regency - Tjahyadi, I Gede Ketut Deny Patmantha Putra; Budhitresna, Anak Agung Gede; Suka Astini, Dewa Ayu Agung Alit (UNUSA Press, 2024)
Background: Being overweight or obese is one of the factors that cause an increase in blood pressure. The bigger a person's body, the more blood is needed to supply nutrients and oxygen to other tissues and muscles. Bali Province, especially Gianyar Regency, has a relatively high number of hypertension sufferers. The highest estimate of hypertension sufferers is in the working area of the Sukawati I Public Health Center, with a prevalence of 8.55% of the total in Gianyar Regency of 17.35%. This research aims to determine the relationship between body mass index and blood pressure control in hypertensive patients at the Sukawati I Public Health Center, Gianyar Regency. Methods: The research design used was analytic observational with a crosssectional approach. The number of research subjects, namely 83 people, was taken by consecutive sampling technique. Data analysis will be carried out univariately and bivariate using the chi-square test method with a confidence level of 95% (p < 0.05). Results: The results of the univariate analysis showed that the majority of study subjects were aged 51-60 years (60.2%), were female (66.3%), most had normal BMI (66.3%), and 66.3% of subjects with hypertension were classified as have controlled blood control. Based on the results of statistical tests, a value of p = 0.003 (p < 0.05) was obtained, which indicated a significant relationship between body mass index and blood pressure control in hypertensive patients at the Sukawati I Public Health Center, Gianyar Regency. Conclusion: The results of this study indicate that the increasing BMI status of hypertensive patients will tend to have uncontrolled blood pressure.